2022
DOI: 10.1002/ejhf.2743
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and titrating approach of therapy in heart failure with reduced ejection fraction following the 2021 European Society of Cardiology guidelines: an international cardiology survey

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Therefore, Fauvel et al 6 . investigated the opinion of cardiologists on sequencing, titration and optimal timing of all the recommended HFrEF drugs in their work published in this issue of the Journal.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, Fauvel et al 6 . investigated the opinion of cardiologists on sequencing, titration and optimal timing of all the recommended HFrEF drugs in their work published in this issue of the Journal.…”
Section: Figurementioning
confidence: 99%
“…Within this context, the survey by Fauvel et al . provide an important baseline assessment of contemporary cardiologists' thinking 6 . Their results show that most cardiologists and physicians still prefer the conventional uptitration sequence, which largely follows the chronology of clinical trials.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Early start of the four pillars of guideline-directed medical therapies (GDMT) in patients with HF and reduced EF (HFrEF) is strongly suggested. 19,[21][22][23][24] A survey involving 615 cardiologists worldwide showed that the historical sequential approach (angiotensin-converting enzyme inhibitors or angiotensin receptor-neprilysin inhibitors first, beta-blockers second, mineralocorticoid receptor antagonists third, and sodium-glucose [22][23][24][25][26] A cost-effectiveness analysis showed that immediate versus 12-month delayed initiation of dapagliflozin is associated with almost 10% additional quality-adjusted life year gain and greater clinical benefits. 27 A consistent increase in haematocrit has been observed following the initiation of SGLT2i.…”
Section: Medical Therapymentioning
confidence: 99%